Comparative analysis of sport psychology of sportsman in information technology and human psychology - Muhammad Talal Ahmad; Sonia IKRAM; Aleezaa Masood, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The purpose of this research is to describe the comparative analysis related to the sport psychology of sportsmen in information technology also that human psychology. This research was conducted in china for deermine. The research study used specific questions related to the variables. In this research, the sports psychology of sportsmen, information technology, and human psychology are all considered indicators. For measuring, the study used AMOS and smart PLS software and ran different results, including minimization history, the assessment of normality, correlation coefficient, covariance, significant analysis, and total effects; it also describes the graphical analysis for measuring the relationship with each other. According to the result, information technology shows positive and significant relation to the sports psychology of sportsmen. On the other hand, information technology shows that harmful, but it's a substantial effect on human psychology. Therefore, sport psychology represents direct and significant relation with human psychology.